An observational study of the prevalence of metabolic syndrome in treatment-experienced people living with HIV in Singapore - Ang, Li Wei; Ng, Oon Tek; Boudville, Irving Charles; Leo, Yee Sin; Wong, Chen Seong (PLOS ONE, 2021)
Background While the use of combination antiretroviral therapy (cART) has conferred significant reduction in morbidity and mortality, there are growing concerns about the metabolic complications of antiretroviral regimens in HIV-infected patients. The aim of this study was to estimate the prevalence of metabolic syndrome (MetS) among people living with HIV (PLHIV) in Singapore. Methods We conducted a retrospective study using the clinical database maintained by the Clinical HIV Programme at the National Centre for Infectious Diseases, Singapore. Treatment-experienced PLHIV on follow-up during 2015–2017 were included. MetS was defined as having three or more of the following five abnormalities: hypertriglyceridemia, HDL hypocholesterolemia, hypertension, obesity, and diabetes. Results A total of 2,231 PLHIV were included in this study. 93.9% were men, and the median age at latest follow-up was 48 years. The median duration of HIV infection and duration of exposure to cART was 6.8 years and 5.7 years, respectively. All had been exposed to nucleoside reverse transcriptase inhibitors (NRTIs) as the first line of treatment, 93.9% to non-NRTIs, 28.6% to protease inhibitors (PIs) and 12.8% to integrase strand transfer inhibitors. The most common metabolic abnormality among PLHIV was HDL hypocholesterolemia (60.2%) followed by hypertriglyceridemia (45.5%). Of all the 2,231 individuals, 68.8% had at least one component of MetS. The overall prevalence of MetS was 23.6% (95% confidence interval 21.9%–25.4%). Of the 526 with MetS, the most common combination was HDL hypocholesterolemia, hypertriglyceridemia and hypertension (51.0%), followed by HDL hypocholesterolemia, hypertriglyceridemia, hypertension and diabetes (25.1%). Compared with PLHIV without MetS, a significantly higher proportion of those with MetS were ever on protease inhibitors (33.5% vs. 27.1%). Conclusion MetS is common in PLHIV. In view of the progressive aging of HIV-infected population and long-term use of cART, regular monitoring for metabolic abnormalities, surveillance of drug effects and behavioural interventions are needed to optimize management and prevention of metabolic disorders in PLHIV.